Is The Instagram as A Homestay Selection in A Tourist Village? - Mustika, Amalia; Ratu Bilqis, Linda Desafitri; Habibie, Fachrul Husain (Jurnal Penelitian Pariwisata, 2024)
This research explores how Instagram is used to find homestay information in tourist village areas. Using a descriptive method and quantitative approach, data were collected through field surveys, Google Forms, and in-person interviews with participants from Jakarta.. The findings show that women prefer Instagram over men due to its image-centric nature, and young people aged 16-25 find it useful for homestay searches. Nonetheless, 27% of respondents express disagreement, stating that they primarily use Instagram for archiving photos and videos and favor online travel agent apps for booking accommodations. Nevertheless, 73% of participants concur that Instagram's features streamline the process of finding homestays. This study contributes to the tourism sector by highlighting Instagram’s potential to enhance homestay visibility, which could help improve the household economy in tourist villages. Keywords: Instagram, homestay, tourist village